2016
DOI: 10.1038/nature20802
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants regulating expression levels and isoform diversity during embryogenesis

Abstract: Embryonic development is driven by tightly regulated patterns of gene expression, despite extensive genetic variation among individuals. Studies of expression quantitative trait loci (eQTL) indicate that genetic variation frequently alters gene expression in cell-culture models and differentiated tissues. However, the extent and types of genetic variation impacting embryonic gene expression, and their interactions with developmental programs, remain largely unknown. Here we assessed the effect of genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 32 publications
12
55
0
Order By: Relevance
“…Our study substantially extends on previous work6,7 by demonstrating widespread functional consequences of genetic variation for many molecular and cellular phenotypes in human pluripotent stem cell lines, including in the efficiency with which iPS cells differentiate4143. This is potentially a consequence of variation in core components of the regulatory networks controlling cellular differentiation and responses to external environmental stimuli, as observed previously in hematopoietic cells and mouse and fly embryos4446.…”
Section: Discussionsupporting
confidence: 84%
“…Our study substantially extends on previous work6,7 by demonstrating widespread functional consequences of genetic variation for many molecular and cellular phenotypes in human pluripotent stem cell lines, including in the efficiency with which iPS cells differentiate4143. This is potentially a consequence of variation in core components of the regulatory networks controlling cellular differentiation and responses to external environmental stimuli, as observed previously in hematopoietic cells and mouse and fly embryos4446.…”
Section: Discussionsupporting
confidence: 84%
“…57 One can anticipate that development-stage-specific eQTLs also exist in humans, as it has been reported in Drosophila. 58 Altogether, these studies revealed important recurrent features of the thousands of eQTLs found in different tissues. Thus, almost 60%-80% of genes have at least one eQTL, 64 mostly cis-acting usually within 1 Mb of the transcription start site (TSS).…”
Section: Demographic and Evolutionary Forcesmentioning
confidence: 90%
“…Sex and age effects have also been identified . One can anticipate that development‐stage‐specific eQTLs also exist in humans, as it has been reported in Drosophila …”
Section: Genome‐wide Genetic Studies Of Expression Phenotypesmentioning
confidence: 99%
“…Additionally, responses to tunicamycin were mapped using the Drosophila Genetic Reference Panel [30] to a large number of loci but none of these loci were shown to play a direct role in the variable drug response [40]. In a global approach, a large-scale expression study of 80 inbred D. melanogaster strains from the Drosophila Genetic Reference Panel found 2,000 genes with variable expression that can be explained by genetic differences in the panel, referred to expression quantitative trait loci or eQTL [41]. Interestingly, significant differences in mRNA expression of approximately 20 glutathione S-transferases (GSTs) and cytochrome P450 genes, which have roles in xenobiotic responses, were observed among these strains, suggesting that natural variability to metabolize xenobiotics likely exists among these strains [41].…”
Section: The Effect Of Genetic Background On Chemotherapeutic Drug Rementioning
confidence: 99%
“…In a global approach, a large-scale expression study of 80 inbred D. melanogaster strains from the Drosophila Genetic Reference Panel found 2,000 genes with variable expression that can be explained by genetic differences in the panel, referred to expression quantitative trait loci or eQTL [41]. Interestingly, significant differences in mRNA expression of approximately 20 glutathione S-transferases (GSTs) and cytochrome P450 genes, which have roles in xenobiotic responses, were observed among these strains, suggesting that natural variability to metabolize xenobiotics likely exists among these strains [41]. As another example, European populations of D. melanogaster harbor a deletion in the 3’ UTR of the metallothionein A ( MtnA ) gene that results in a four-fold increase in MtnA expression [42].…”
Section: The Effect Of Genetic Background On Chemotherapeutic Drug Rementioning
confidence: 99%